Methotrexate and Leflunomide in the Treatment of Rheumatoid Arthritis - Hatice Bodur (Archives of Rheumatology, 2006)
The treatment of rheumatoid arthritis has changed in the last ten years. Methotrexate is an antimetabolite drug and commonly used as the first disease modifying antirheumatic drug (DMARD). Its clinical efficacy and safety profile has been documented and it slows the development of radiological erosions. Leflunomide is also an antimetabolite drug and relatively new. In this review the efficacy, safety, mono and combination therapy of these drugs have been discussed. (Rheumatism 2006; 21: 60-6)